1975
DOI: 10.1002/1097-0142(197510)36:4<1289::aid-cncr2820360415>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cell-mediated immune response in patients with malignant melanoma.I. In vitro lymphocyte reactivity to pha and antigens following immunization

Abstract: In vitro lymphocyte function was evaluated in 61 patients with different clinical stages of malignant melanoma. Thirty‐one of these patients had localized disease, 13 regional metastases, 10 distant lymph node or skin metastases, and 7 visceral metastases. Following immunization, in vitro lymphocyte reactivity to three antigens (diphtheria toxoid, tetanus toxoid and α‐hemocyanin of Helix pomatia) was studied in the presence of autologous serum, in addition to lymphocyte reactivity to phytohemagglutinin (PHA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Golub [9] studied lymphocyte transformation to PHA, pokeweed mitogen (PWM) and ConA in 29 melanoma patients, and found that these patients, as a whole, had decreased responses compared with healthy controls. In a more extensive study assessing blastogenesis to PHA and three antigens (diphtheria, tetanus toxoid, hemocyanin) in 61 melanoma patients, DeGast noted that patients with progressive visceral disease had significantly decreased transformation compared with normal controls as well as patients with minimal disease [5]. In a more extensive study assessing blastogenesis to PHA and three antigens (diphtheria, tetanus toxoid, hemocyanin) in 61 melanoma patients, DeGast noted that patients with progressive visceral disease had significantly decreased transformation compared with normal controls as well as patients with minimal disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…Golub [9] studied lymphocyte transformation to PHA, pokeweed mitogen (PWM) and ConA in 29 melanoma patients, and found that these patients, as a whole, had decreased responses compared with healthy controls. In a more extensive study assessing blastogenesis to PHA and three antigens (diphtheria, tetanus toxoid, hemocyanin) in 61 melanoma patients, DeGast noted that patients with progressive visceral disease had significantly decreased transformation compared with normal controls as well as patients with minimal disease [5]. In a more extensive study assessing blastogenesis to PHA and three antigens (diphtheria, tetanus toxoid, hemocyanin) in 61 melanoma patients, DeGast noted that patients with progressive visceral disease had significantly decreased transformation compared with normal controls as well as patients with minimal disease [5].…”
Section: Discussionmentioning
confidence: 99%